2015
DOI: 10.1080/00014788.2015.1039476
|View full text |Cite|
|
Sign up to set email alerts
|

Corporate social responsibility, country-level predispositions, and the consequences of choosing a level of disclosure

Abstract: We study the different levels of corporate social responsibility (CSR) disclosures of the largest European firms. We find that firms are more predisposed to disclose more CSR information in countries with: better investor protection, higher levels of democracy, more effective government services, higher quality regulations, more press freedom, and a lower commitment to environmental policies. Our analysis of the association of different levels of CSR disclosure with share prices indicates that a high level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
127
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 250 publications
(141 citation statements)
references
References 44 publications
11
127
0
3
Order By: Relevance
“…In this sense, voice and accountability are the reflection of the degree of democracy and freedoms. One can conclude that such a liberal context can ensure and produce higher non-financial and social disclosures as outcomes (De Villiers and Marques [61]). Since companies today fill the social void by offering other services, and since they increasingly play public roles, a democracy ideal would require that these organizations are subject to some form of regulation to "blend" their financial goals with their social and political commitment goals-CSR (Hussain and Moriarty [101]).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this sense, voice and accountability are the reflection of the degree of democracy and freedoms. One can conclude that such a liberal context can ensure and produce higher non-financial and social disclosures as outcomes (De Villiers and Marques [61]). Since companies today fill the social void by offering other services, and since they increasingly play public roles, a democracy ideal would require that these organizations are subject to some form of regulation to "blend" their financial goals with their social and political commitment goals-CSR (Hussain and Moriarty [101]).…”
Section: Discussionmentioning
confidence: 99%
“…One can conclude that such a liberal context can ensure and produce as outcome higher non-financial and social disclosures. De Villiers and Marques [61], found that firms are more committed to social disclosures in countries with higher levels of democracy, rather than those which operate in a restricted or unstable context.…”
Section: Voice and Accountabilitymentioning
confidence: 99%
See 3 more Smart Citations